Adherence to COVID-19 preventive measures in Sub-Saharan Africa during the 1st year of the pandemic: Pooled analysis of the International Citizen Project on COVID-19 (ICPCovid) surveys - Ngarka, Leonard; Siewe Fodjo, Joseph Nelson; Njamnshi, Wepnyu Yembe; Ditekemena, John D.; Ahmed, Mohammed A. M.; Wanyenze, Rhoda K.; Dula, Janet; Sessou, Philippe; Happi, Christian T.; Nkengasong, John N.; Colebunders, Robert; Njamnshi, Alfred K. (Frontiers in Public Health, 2022)
Introduction While most governments instituted several interventions to stall the spread of COVID-19, little is known regarding the continued observance of the non-pharmaceutical COVID-19 preventive measures particularly in Sub-Saharan Africa (SSA). We investigated adherence to these preventive measures during the initial 6 months of the COVID-19 outbreak in some SSA countries. Methods Between March and August 2020, the International Citizen Project on COVID-19 consortium (www.icpcovid.com) conducted online surveys in six SSA countries: Benin, Cameroon, Democratic Republic of Congo, Mozambique, Somalia, and Uganda. A five-point individual adherence score was constituted by scoring respondents' observance of the following measures: mask use, physical distancing, hand hygiene, coughing hygiene, and avoiding to touch one's face. Community behaviors (going to public places, traveling during the pandemic) were also assessed. Data were analyzed in two time periods: Period 1 (March-May) and Period 2 (June-August). Results Responses from 26,678 respondents were analyzed (mean age: 31.0 ± 11.1 years; 54.1% males). Mean individual adherence score decreased from 3.80 ± 1.37 during Period 1, to 3.57 ± 1.43 during Period 2; p < 0.001. At the community level, public events/places were significantly more attended with increased travels during Period 2 compared to Period 1 (p < 0.001). Using linear mixed models, predictors of increased individual adherence included: higher age (Coef = 0.005; 95% CI: 0.003–0.007), female gender (Coef = 0.071; 95% CI: 0.039–0.104), higher educational level (Coef = 0.999; 95% CI: 0.885–1.113), and working in the healthcare sector (Coef = 0.418; 95% CI: 0.380–0.456). Conclusion Decreasing adherence to non-pharmaceutical measures over time constitutes a risk for the persistence of COVID-19 in SSA. Younger persons and those with lower education levels constitute target groups for improving adherence to such measures.